A novel approach for characterization of KSHV‐associated multicentric Castleman disease from effusions. (20th October 2022) - Zhou, Ting; Yuan, Constance M.; Lurain, Kathryn; Rous, Clarissa; Weaver, Linda; Raffeld, Mark; Stetler‐Stevenson, Maryalice; Uldrick, Thomas S.; Filie, Armando C.; Pittaluga, Stefania; Jaffe, Elaine S.; Marshall, Vickie; et al.
Summary: A biopsy of lymphoid tissue is currently required to diagnose Kaposi sarcoma‐associated herpesvirus (KSHV)‐associated multicentric Castleman disease (KSHV–MCD). Patients showing clinical manifestations of KSHV–MCD but no pathological changes of KSHV–MCD are diagnosed as KSHV inflammatory cytokine syndrome. However, a lymph node biopsy is not always feasible to make the distinction. A pathognomonic feature of lymph nodes in KSHV–MCD is the expansion of KSHV‐infected, lambda‐restricted but polyclonal plasmablasts. To investigate whether these cells also reside in extra‐nodal sites, effusion from 11 patients with KSHV–MCD and 19 with KSHV inflammatory cytokine syndrome was analysed by multiparametric flow cytometry. A distinct, lambda‐restricted plasmablastic population (LRP) with highly consistent immunophenotype was detected in effusions in 8/11 patients with KSHV–MCD. The same population was also observed in 7/19 patients with KSHV inflammatory cytokine syndrome. The detection of LRP stratified KSHV inflammatory cytokine syndrome into two clinically distinct subgroups; those with detectable LRP closely resembled KSHV–MCD, showing similar KSHV viral load, comparable severity of thrombocytopenia and hypoalbuminaemia, and similar incidences of hepatosplenomegaly. Collectively, the detection of LRP by flow cytometry can serve as a valuable tool in diagnosing KSHV–MCD. KSHV inflammatory cytokine syndrome with LRP in effusions may represent a liquid‐form of KSHV–MCD.